Delivery of RALA/siFKBPL nanoparticles via electrospun bilayer nanofibres: An innovative angiogenic therapy for wound repair - Mulholland, Eoghan J.; Ali, Ahlam; Robson, Tracy; Dunne, Nicholas J.; McCarthy, Helen O. (Journal of controlled release, 2019)
[Display omitted] FK506-binding protein-like (FKBPL) has previously been shown to inhibit angiogenesis viain vitro and in vivo experimentation. Thus, it was proposed that the delivery of a siRNA targeting FKBPL could hold great potential in promoting angiogenesis for advanced wound healing applications. An effective delivery system has been utilised to encapsulate the siFKBPL to form nanoparticles, thereby improving cellular entry and eliciting a potent angiogenic response. In this study, nanoparticles were formed via condensation of siFKBPL with RALA; a novel, cationic 30 mer amphipathic peptide. Nanoparticles prepared at a N:P ratio of 6 demonstrated an average particle size of 76.6nm with a zeta potential of +16.5mV. Treatment of HMEC-1 cells at N:P 6 resulted in a transfection efficiency of 33.7%, negligible cytotoxicity, and significant knockdown of endogenous FKBPL expression. Functionally, treatment with RALA/siFKBPL resulted in significant improvements in cell migration and endothelial tubule formation in vitro. The process of electrospinning was employed to fabricate a nanofibrous wound patch to facilitate the controlled delivery of the RALA/siFKBPL nanoparticles. Alginate/poly-(vinyl alcohol) was electrospun following electrospinning of Chitosan/poly-(vinyl alcohol) to form a bilayered wound patch. Subsequently, the nanofibres were crosslinked to improve stability, before nanoparticle incorporation via soak loading. In vivo wound healing studies using C57BL/6J mice demonstrated a significant increase in angiogenesis when the RALA/siFKBPL nanoparticles were delivered from the bilayered wound patch; a 326% increase in blood vessel density was observed compared to untreated wounds. Taken together, this data demonstrates that delivery of RALA/siFKBPL nanoparticles from the bilayered wound patch represents an innovative wound healing therapy.